Pickering Emulsion Properties Generated by Nanofibrillated Cellulose Isolated from Oil Palm Fruit Bunch (OPEFB) as a Stabilizer - Ira Desri Rahmi; Erliza Hambali; Farah Fahma; Dwi Setyaningsih (Green Engineering Society, 2023)
This study aims to find the optimal nanofibrillated cellulose (NFC) concentration isolated from oil palm empty fruit bunch (OPEFB) particles to form stable pickering emulsions against creaming and coalescence. The emulsification process is based on a combination of homogenizer and ultrasonication. Pickering emulsion was prepared by mixing the dispersed phase (palm oil) and the dispersing phase (NFC concentration of 0.05 - 0.7 w/v%) at the ratio of 10:90. Fresh emulsion has a milky white appearance and is homogeneous. However, some samples' creaming process occurred on the 30th day of storage. Microscopic observations show that the droplets are round with various sizes. Differences in NFC concentrations significantly affect droplet size, zeta potential, rheology, and emulsion stability. Increasing the NCF concentration resulted in smaller droplet sizes, viscosity, zeta potential, and pickering emulsion stability. The emulsion has high stability against coalescence and creaming. NFC at 0.7 w/v% generates an emulsion with the best characteristics and high stability against creaming and coalescence. OPEFB-based NFC has the potential as a pickering emulsion stabilizer particle that can be applied to the food and non-food industries.